A phosphorus/silicon/triazine‐containing flame retardant towards flame retardancy and mechanical properties of epoxy resin. Issue 31 (2nd June 2022) - Hou, Zhuang; Cai, Haopeng; Li, Chuan; Li, Bolun; Wang, Huihuan
Abstract: A phosphorous/silicon/triazine‐containing flame retardant named DTD is synthesized and provides epoxy resin with enhanced flame retardancy and mechanical properties simultaneously. The modified epoxy with the DTD content of 18.1 wt% shows excellent flame retardancy, manifested in the limited oxygen index (LOI) value of 36.6% with UL‐94 V‐0 rating obtained. In the cone calorimeter test, its peak heat release rate (PHRR), total heat release (THR) and average effective heat of combustion (av‐EHC) are reduced by 43.7%, 45.0%, and 38.1% compared with neat epoxy resin, respectively. Besides, DTD exhibits a good charring capability, indicated by observation of an expanded char layer structure and the 160.3% increment in char residue after the cone calorimeter test. The mode of action of DTD is explained by the analysis of char residue and the pyrolysis behavior in the gas phase. In addition, DTD has good compatibility with epoxy resin, confirmed by single spike of tan delta and similar half‐peak width in dynamic mechanical analysis. While improving the flame retardancy, DTD also enhances the mechanical properties of epoxy resin. With 8.8 wt% of DTD content, the modified epoxy resin possesses desirable mechanical properties, with 36.0% and 18.9% increase in tensile strength and flexural strength, respectively. Abstract : The phosphorus/silicon/triazine‐containing flame retardant (DTD) endowing epoxy resin with excellent flame retardancy and enhanced mechanical properties.